Weight of evidence approach in dredge material management: What is it and how is it used? A UK perspective - Jemma-Anne Lonsdale; Simone de Winter; Joe Perry; Claire Mason; Charlotte Clarke; Sylvia Blake; Kirsty Clarke (Marine Policy, 2026)

Resistance exercise with combined Valsalva manoeuvre acutely increases carotid-femoral pulse wave velocity in healthy untrained individuals - Blake G. Perry; Melissa J. Perry; Riley Dixon; Michael Bush; Helen Ryan-Stewart (European Journal of Applied Physiology, 2026)
Purpose The Valsalva manoeuvre (VM) may contribute to the observed increase in pulse wave velocity (PWV) following resistance exercise (RE). However, VM use during RE is rarely reported or discussed in the literature. We compared the acute carotid-femoral PWV response before and following RE with paced breathing, RE with a VM (REVM) and the VM alone. Methods 15 healthy RE-untrained participants (female = 8) (mean ± SD: age, 24 ± 5 years; height, 171.7 ± 10.9 cm; body mass 69.6 ± 14.5 kg) completed in a randomised order (1) RE: 3 sets of 10 repetitions of 4 RE exercises at 60% of 1RM with paced breathing (2) REVM: repetition of the RE requirements with a VM during each of the last 6 repetitions of each set (3) VM: 12 sets of 6, 3 s VMs at a mouth pressure of 40 mm Hg. PWV was measured pre- and post-condition, with mean middle cerebral artery blood velocity, mean arterial blood pressure (MAP), heart rate, and partial pressure of end-tidal carbon dioxide measured during each visit. Results An interaction effect for PWV ( P = 0.024) was observed, with post hoc tests revealing increased PWV post REVM ( P = 0.006, pre 5.4 ± 0.3 vs. post 6.1 ± 0.9 cm/s) and VM ( P = 0.031, 5.7 ± 0.8 vs. 6.0 ± 1.0 cm/s), but not RE ( P = 0.957, 5.7 ± 0.6 vs. 5.7 ± 0.8). REVM produced the greatest MAP increase from baseline (Δ37 ± 15 mm Hg, P < 0.05 vs. both RE and VM). Conclusion These findings indicate that the VM contributes to the acute rise in post RE PWV when performed during RE and acutely increases PWV when performed repeatedly in isolation (Trial registration number ACTRN12624000876594, Date of registration 18/07/2024). Trial registration number ACTRN12624000876594.

Correction: Resistance exercise with combined Valsalva manoeuvre acutely increases carotid-femoral pulse wave velocity in healthy untrained individuals - Blake G. Perry; Melissa J. Perry; Riley Dixon; Michael Bush; Helen Ryan-Stewart (European Journal of Applied Physiology, 2026)

High-intensity exercise training mitigates post-exercise orthostatic hypotension in men - Tze-Huan Lei; Hao-Yu Li; Richie P. Goulding; Faming Wang; Tatsuro Amano; Tomomi Fujimoto; Naoto Fujii; Narihiko Kondo; Blake Perry; Toby Mündel (European Journal of Applied Physiology, 2026)

Evaluating the coral microbiome during cryopreservation - Tori Jefferson; E. Michael Henley; Patrick M. Erwin; Claire Lager; Riley Perry; Darya Chernikhova; Matthew J. Powell-Palm; Blake Ushijima; Mary Hagedorn (Cryobiology, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Cerebrovascular, cardiovascular and strength responses to acute ammonia inhalation - Blake G. Perry; Hayden J. Pritchard; Matthew J. Barnes (European Journal of Applied Physiology, 2016)

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

The effects of vibration therapy on muscle force loss following eccentrically induced muscle damage - Matthew J. Barnes; Blake G. Perry; Toby Mündel; Darryl J. Cochrane (European Journal of Applied Physiology, 2012)

QTL, additive and epistatic effects for SCN resistance in PI 437654 - Xiaolei Wu; Sean Blake; David A. Sleper; J. Grover Shannon; Perry Cregan; Henry T. Nguyen (Theoretical and Applied Genetics, 2009)